2018
DOI: 10.1002/jcp.26874
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Zerumbone inhibits epithelial‐mesenchymal transition and cancer stem cells properties by inhibiting the β‐catenin pathway through miR‐200c

Abstract: Colorectal cancer (CRC) is one of the most lethal and rampant human malignancies in the world. Zerumbone, a sesquiterpene isolated from subtropical ginger, has been found to exhibit an antitumor effect in various cancer types. However, the effect of Zerumbone on the biological properties of CRC, including epithelial-mesenchymal transition (EMT) and cancer stem cells (CSCs) has not been fully elucidated. Here, we investigated the inhibitory action of Zerumbone on the EMT process, CSC markers, and the β-catenin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…Liu et al [51] showed that CD146 decreased the drug resistance of colorectal cancer by functioning as a suppressor of cancer stemness through inactivating the Wnt/β-catenin cascade. It was also observed that zerumbone could suppress the stemness properties of CRC by inhibiting the β-catenin signaling pathway [52]. These studies all suggested that the Wnt/β-catenin signaling pathway plays crucial roles in fostering chemoresistance of CRC through stemness.…”
Section: Wnt/β-catenin Signaling and Colorectal Cancer Stem Cells In mentioning
confidence: 87%
“…Liu et al [51] showed that CD146 decreased the drug resistance of colorectal cancer by functioning as a suppressor of cancer stemness through inactivating the Wnt/β-catenin cascade. It was also observed that zerumbone could suppress the stemness properties of CRC by inhibiting the β-catenin signaling pathway [52]. These studies all suggested that the Wnt/β-catenin signaling pathway plays crucial roles in fostering chemoresistance of CRC through stemness.…”
Section: Wnt/β-catenin Signaling and Colorectal Cancer Stem Cells In mentioning
confidence: 87%
“…A recent study by Dermani et al showed that zerumbone treatment of HCT116 and SW48 colorectal cell lines inhibited cell viability, migration, invasion and sphere-forming potential via miR-200c [32]. Silencing of miR-200c reduced the anti-cancer effects of zerumbone.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that zerumbone inhibited the β-catenin pathway via miR-200c to block EMT and cancer stem cells. 26 In addition, nicotine upregulated FGFR3 and RB1 and promoted EMT by the downregulation of miR-99b and miR-192 in non-small-cell lung cancer cells. 50 Moreover, osthole alleviated EMT-mediated metastasis by inhibiting miR-23a-3p.…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%
“…Zerumbone from Zingiber zerumbet (L.) Smith exhibited anti‐inflammatory and anticancer properties. Recently, it was reported that zerumbone inhibited the β‐catenin pathway via miR‐200c to block EMT and cancer stem cells . In addition, nicotine upregulated FGFR3 and RB1 and promoted EMT by the downregulation of miR‐99b and miR‐192 in non–small‐cell lung cancer cells .…”
Section: Small Molecules Against Emtmentioning
confidence: 99%